CTE in Athletes: Understanding the Long-Term Effects of Repetitive Head Injuries - Weronika Sepioło; Mikołaj Lewandoswki; Zofia Kwiatkowska; Wojciech Kurkiewicz; Oskar Woźniak; Jowita Mikulska; Joanna Wąsik; Kacper Gryboś; Julia Kiełbratowska (Quality in Sport)
Introduction and PurposeChronic traumatic encephalopathy (CTE) is a progressive neurodegenerative disease linked to repeated head injuries such as concussions and sub-concussive impacts [19]. Initially observed in retired boxers with behavioral and cognitive symptoms, it was called “punch-drunk syndrome” [3,9,16]. CTE is mostly found in athletes from contact sports (e.g., football, boxing, hockey, rugby) and in military personnel [1,3,9,13,19]. While most reported cases involve male athletes, anyone exposed to repetitive head injury (RHI) is at risk [2,10,13]. Due to increasing awareness of its long-term effects on brain health, CTE is now a critical topic in sports medicine, neurology, and public health.